The Radioprotective Effect of LBP on Neurogenesis and Cognition after Acute Radiation Exposure - Yin, Gang; Wang, Qinqi; Lv, Tongtong; Liu, Yifan; Peng, Xiaochun; Zeng, Xianqin; Huang, Jiangrong (Current Radiopharmaceuticals, 2024)
Background: Radiation exposure has been linked to the development of brain damage and cognitive impairment, but the protective effect and mechanism of Lycium barbarum pills (LBP) on radiation-induced neurological damage remains to be clarified. Methods: Behavioral tests and immunohistochemical studies were conducted to evaluate the protective effects of LBP extract (10 g/kg orally daily for 4 weeks) against radiation-induced damage on neurogenesis and cognitive function in Balb/c mice exposed to 5.5 Gy X-ray acute radiation. Results: The results showed that the LBP extract significantly improved body weight loss, locomotor activity and spatial learning and memory. Immunohistochemical tests revealed that the LBP extract prevented the loss of proliferating cells, newly generated neurons and interneurons, especially in the subgranular area of the dentate gyrus. Conclusion: The findings suggest that LBP is a potential neuroprotective drug for mitigating radiation-induced neuropsychological disorders.
Keywords: cognitive impairment